Kinetics of maternally-derived serogroup A, C, Y and W-specific meningococcal immunoglobulin G in Malian women and infants. Issue 18 (24th April 2019) - Findlow, H.; Tapia, M.D.; Sow, S.O.; Haidara, F.C.; Coulibaly, F.; Keita, A.M.; Diallo, F.; Doumbia, M.; Traore, A.; Schluterman, N.; Clark, D.A.; Borrow, R.; et al.
Highlights: Immunisation with MCV during pregnancy resulted in an antibody response. Maternal immunization with MCV conveyed protective levels of MenA IgG at birth. Infant antibody levels declined over the first 3 months of life. Abstract: A prospective, randomised, controlled observer-blind trial measuring the efficacy and immunogenicity of trivalent influenza vaccine (TIV) and the immunogenicity of quadrivalent meningococcal conjugate vaccine (MCV) in pregnant women and their infants up to 6 months of age was conducted in Mali. Here we reported the immunogenicity of MCV, which was used as a comparator vaccine to TIV, in this population. Third-trimester pregnant Malian women were randomized to receive TIV or MCV. Blood samples were collected from women prior to vaccination, 28 days post-vaccination, at delivery and 3 and 6 months post-delivery and from infants at birth and 3 and 6 months of age. Meningococcal-specific serogroup (Men) A, C, Y and W-specific antibodies were measured by enzyme linked immunosorbent assay in a randomly selected subset of 50 mother-infant pairs where the mother had received MCV. At birth, 94.0% (47/50) of infants had MenA specific IgG levels ≥ 2 µg/mL decreasing to 72.9% and 30.4% at 3 and 6 months of age. For MenC, 81.3% (39/48) of infants had MenC specific IgG levels ≥ 2 µg/mL at birth decreasing to 29.4% and 17.8% at 3 and 6 months of age. For MenY, 89.6% (43/48) of infants had MenY specific IgG levels ≥ 2 µg/mL at birth decreasing to 64.6% and 62.5% at 3 and 6 months of age. For MenW, 89.6% (43/48) of infants had MenW specific IgG levels ≥ 2 μg/ml at birth decreasing to 62.5% and 41.7% at 3 and 6 months of age. Maternal immunization with MCV conveyed protective levels of IgG at birth through to 3 months of age in the majority of infants.